IV.i.5. Letters relating to George Wolfe's property Acomb Priory in Yorkshire - Cooper, T. P., active 1913; Wolfe, George, 1859-1941 (1913)
Contains a letter from T. P. Cooper of Wentworth Road, York, concerning a window at the Priory (17 Oct. 1913) and an incomplete letter from Wolfe (recipient unclear) concerning maintenance work on the property (3 Feb. 1921).
Keywords: Wolfe, George, -- 1859-1941